A Comparison of Computer-Based Bibliographic Database Searching vs. Manual Bibliographic Searching. Final CARE Grant Report #5964 - Pritchard, Eileen E.; Rockman, Ilene F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The purpose of this study was to improve upon previous research investigations by analyzing the elements of cost effectiveness, precision, recall, citation overlap, and hours searching in a comparison between computerized database searching and manual searching, using the setting of an academic library environment with a diverse group of students as subjects. Students enrolled in Library 301 (computer searching) during four academic quarters in 1985 and 1986 at two California colleges provided the laboratory sample for the data collection (N=64). The students were introduced to three weeks of instruction on the concepts of manual search searching and three weeks on automated search techniques and strategies. The remaining four weeks were spent applying the knowledge to a research project that required using both types of search skills. The results indicated that: (1) contrary to previous studies, in most cases online searching was not a cost-effective method for retrieving data; (2) higher recall occurred online, while higher precision occurred through manual searching; (3) the citation overlap between the two sources was 2.9%; and (4) more time was spent searching manually than online. Areas identified for further research include the relationship between satisfaction and precision (high satisfaction is not synonymous with high precision); the influence of multiple instrumental strategies on search output; and the relationship between the number of relevant items found and the time expended. Data are compiled in seven tables and a 16-item bibliography is provided. (SD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Bibliographic Databases; Comparative Analysis; Cost Effectiveness; Indexes; Information Retrieval; Online Systems; Search Strategies; User Needs (Information); User Satisfaction (Information); Reports, Research